KERJASAMA INDONESIA-AUSTRALIA DI SEKTOR PERIKANAN DALAM MENANGGULANGI PERMASALAHAN ILLEGAL, UNREPORTED, UNREGULATED (IUU) FISHING DI LAUT TIMOR AUSTRALIA TAHUN 2017-2021 - Chenika Fricila (2022)
Indonesia and Australia are two countries that are actively cooperating in the fisheries sector with the aim of tackling Illegal, Unreported, and Unregulated (IUU) fishing. IUU fishing is the most significant threat to the fisheries sector of the two countries, causing losses in various sectors. Despite that both countries have taken many approaches and policies, the number of IUU fishing case is still remain high. One area that is vulnerable to these activities is the Timor Sea in Australia because it is directly adjacent to the Indonesian sea which makes it easier for fishermen to do IUU fishing. This research was conducted with the aim of knowing whether the realization of the cooperation that has been implemented has succeeded in reducing the transnational crime of IUU fishing that occurred in the Australian Timor Sea. This study uses qualitative approach and descriptive type of research that uses 2 data sources, namely primary and secondary. In analyzing this research, the author uses bilateral cooperation theory, maritime security and IUU fishing concept. The results of this study indicated that the realization of the cooperation that has been carried out by Indonesia and Australia in the fisheries sector as an effort to tackle IUU fishing in 2017-2021 has not been able to reduce IUU fishing cases in Australian Timor Sea Australia because of the economic factors of Indonesian fishermen who are affected by the COVID-19 pandemic.